PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT DENGAN PENCEGAHAN PENYAKIT DEMAM BERDARAH DENGUE - Miftah Apriani; Tridamayanti Tridamayanti (Jurnal 'Aisyiyah Medika, 2019)
Background: Dengue Hemorrhagic Fever (DHF) or Dengue Hemorrhagic Fever (DHF) is currently one of the public health problems in Indonesia which tends to increase the number of patients and the wider spread. Dengue hemorrhagic fever is an infectious disease caused by dengue virus with clinical manifestations of fever, muscle pain / joint pain accompanied by rashes, thrombocytopenia and hemorrhagic thesis. The data obtained amounted to 81 people. Objective: The objective is to determine the relationship of knowledge, habits of hanging clothes and frequency of draining tubs with the prevention of Dengue Hemorrhagic Fever (DHF). Method: This research was conducted at the Puskesmas Service conducted on May 14 until May 25, 2019. Data analysis used univariate and bivariate analyzes. This research method uses analytical survey method with cross sectional approach. The sample in this study amounted to 81 people using systematic random sampling techniques. Results: From the analysis it was found that there was a relationship of knowledge (ρ-value 0.001), habit of hanging clothes (ρ-value 0.001), and frequency of draining tub (p-value 0,000), with the prevention of DHF. Suggestion: in order to increase counseling about the dangers of dengue fever to the public. Keywords: Dengue Hemorrhagic Fever, Behavior